Harnessing primary, secondary and tertiary genepools for durable wheat disease resistance - Anisa Blower; Rumiana V. Ray; Stephen Rawsthorne; Phil J. Howell; Fiona J. Leigh; Kostya Kanyuka (Theoretical and Applied Genetics, 2025)
Bread wheat ( Triticum aestivum ), a cornerstone of global food security contributing ~ 20% of daily caloric intake, faces increasing vulnerability to rapidly evolving pathogens. This is due in part to a narrowed genetic base following domestication and modern breeding. Wild and ancestral wheat relatives are critical reservoirs of disease resistance genes for breeding new, resilient varieties. This review explores the contributions of primary, secondary, and tertiary genepools of wheat to disease resistance, highlighting loci effective against fungal pathogens that threaten European wheat production. It examines the challenges of alien gene transfer including crossability barriers, hybrid necrosis, and suppressor loci and reviews modern breeding tools such as marker-assisted selection, genomic selection, and genome editing for harnessing exotic germplasm. By synthesising current knowledge, this review highlights the vital contribution of ancestral wheat germplasm in enhancing the resilience and productivity of future wheat crops against increasing biotic stresses.

Impact of an SGLT2-loss of function mutation on renal architecture, histology, and glucose homeostasis - Corey B. Hughes; George M. Mussman; Phil Ray; Robert C. Bunn; Virgilius Cornea; Kathryn M. Thrailkill; John L. Fowlkes; Iuliana Popescu (Cell and Tissue Research, 2021)

Governing in the Anthropocene: are there cyber-systemic antidotes to the malaise of modern governance? - Ray Ison; Jason Alexandra; Phil Wallis (Sustainability Science, 2018)